Montenegro : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Montenegro. (IMF Staff Country Reports; Country Report ;, 2016)
This report highlights the recent economic developments and outlook and risks related to the Montenegro's economy. It also discusses policies which need to be implemented to boost growth. Montenegro's economy has rebounded in the past year, and strong growth looks set to continue in 2016, at slightly more than 4 percent. Although the government's growth strategy can bring substantial gains, it also carries sizable risks, notably to the public finances. The authorities have taken various policy measures to (1) contain fiscal sustainability risks, (2) sustainably revitalize credit conditions, (3) safeguard financial sector stability, and (4) boost competitiveness and economic flexibility.